Mental Disorders Are Associated With Leukocytes Telomere Shortening Among People Who Inject Drugs - Durand, Mélusine; Nagot, Nicolas; Michel, Laurent; Le, Sao Mai; Duong, Huong Thi; Vallo, Roselyne; Vizeneux, Amélie; Rapoud, Delphine; Giang, Hoang Thi; Quillet, Catherine; Thanh, Nham Thi Tuyet; Hai Oanh, Khuat Thi; et al. (Frontiers in Psychiatry, 2022)
Premature biological ageing, assessed by shorter telomere length and mitochondrial DNA (mtDNA) alterations, have been reported among people with major depressive disorders or psychotic disorders. However, these markers have never been assessed among people who inject drugs (PWID), although mental disorders are highly prevalent in this population which, in addition, is subject to other aggravating exposures. Diagnosis of mental disorders was performed by a psychiatrist using the MINI test among active PWID in Haiphong, Vietnam. MtDNA copy number (MCN), mtDNA deletion (MDD) and telomere length (TL) were assessed by qPCR and compared to those without any mental disorder. We next performed multivariate analysis to identify risk factors associated if being diagnosed with major depressive episode (MDE) or psychotic syndrome. 130 and 136 PWID with and without psychiatric conditions were analyzed. Among PWID with mental disorders, 110 and 74 were diagnosed with MDE and PS, respectively. Telomere attrition was significantly associated with HCV-infected PWID with MDE or psychotic syndrome (adjusted OR : 0.51 [0.34 ; 0.76] and 0.61 [0.41 ; 0.92], respectively).Telomere attrition was even stronger when PWID cumulated at least two episodes of major depressive disorders. On the other hand, no difference was observed for mtDNA alterations between groups. The telomeric age difference with drug users without diagnosis of psychiatric condition was estimated at 7 to 16 years according to the number of major depressive episodes, making this group more prone to age-related diseases.